Formulation and Evaluation of Nanoscale Solid Lipid Particles Containing a Hydrophilic Drug-Rasagiline Mesylate - Viveksarathi Kunasekaran, Kannan Krishnamoorthy (Journal of Applied Pharmaceutical Science, 2016)
The present study was to prepare and characterize Rasagiline mesylate loaded nanoscale solid lipid particles and evaluate its In-vitro release. Rasagiline mesylate loaded solid lipid nanoparticles was fabricated by microemulsion technique and then characterized with respect to particle size, polydispersity index and zeta potential were measured by photon correlation spectroscopy. Morphological examination was visualized by transmission electron microscopy. The release of Rasagiline mesylate from solid lipid nanoparticles was performed by using the incubator shaking technique. The fabricated formulations particle size ranged from 160.20±3.2 to 210.12±5.3 nm and the zeta potential measurements indicates a narrow size distribution. The Polydispersity index values shown narrow that means the nanoparticles are homogenous in nature. Drug loading and entrapment efficiency of RMSLN-I & RMSLN-II were 33.34±1.45 % & 76.24±1.2 % and 16.67±0.86 % & 73.75±1.02 %, respectively. TEM revealed the particles were monodisperse, uniform size and quasispherical shape. Release of Rasagiline mesylate loaded nanoscale solid lipid particles were shown efficient prolonged drug release and followed by Fickian diffusion mechanism. Furthermore, RM loaded SLNs were found to be stable, after 6 months of storage at different conditions. The developed solid lipid nanoparticles were able to control the drug release for a prolonged period of time.
Keywords: Parkinson disease, Rasagiline mesylate, Solid lipid nanoparticles, Scanning electron microscopy, Transmission electron microscopy.